Ballistic study on the penetration potential and injury potential of different bullet types in the use of a newly developed bullet shooting stunner for adequate stunning of heavy cattle - Gascho, Dominic; Stephan, Roger; Zoelch, Niklaus; Vogt, Michael; Oesch, Michelle Aimée; Thali, Michael; Richter, Henning (Frontiers in Veterinary Science, 2023)
Introduction Recently, a special bullet shooting stunner for heavy cattle has been developed that fires a bullet instead of a bolt. In the search for a suitable ammunition, the following criteria must be met: First, the energy of the bullet must be sufficient to penetrate the thick frontal bones of heavy cattle. Second, the injury potential at the corresponding penetration depth should preferably be large in order to damage brain tissue relevant to stunning. Third, the bullet must not perforate the occipital bone (over-penetration). Methods Four different bullet types [Hornady FTX, Hydra-Shok, Black Mamba, and a common full metal jacket (FMJ) bullet] were evaluated in a series of experiments on soap blocks and removed bone plates followed by computed tomography examinations. Penetration potential was evaluated in terms of kinetic energy relative to the caliber of the bullet, i.e., mean energy density (ED). Injury potential was evaluated by the mean extent of the cavity volume (eCV) at the relevant penetration depth of 5.5 to 7.5 cm in the soap block. Results All four bullet types passed through the frontal bone plate. The ED was 17.50 J/mm2 (Hornady FTX), 17.46 J/mm2 (Hydra-Shok), 13.47 J/mm2 (Black Mamba), and 13.47 J/mm2 (FMJ). The Hornady FTX and the Hydra-Shok each fragmented heavily. The FMJ was excluded after three experiments due to over-penetrations. The eCV was eCV = 3.77 cm2 (Hornady FTX), 2.71 cm2 (Hydra-Shok), and 1.31 cm2 (Black Mamba), with a significant difference (p = 0.006) between the Hornady FTX and the Black Mamba. Discussion For use in heavy cattle, the Hornady FTX and the Hydra-Shok are recommended due to the larger eCV than the Black Mamba.